From the founding word in Parménides to thepersuasive word in Gorgias (Iter, 2022)
In Parménides wefindan intímate relation among being, thinkingandsayingas a metaphysical experienceracionally born, product o f a “divine revelation”. Not separated totally from mythyet, this however, has tum ed nowin an apparel that can express thephilosophers way in solitude to the meeting with the thruth.On the contrary, when philosophy strengthens as dialogue in the V s century athenian democraty, Gorgiasshows that the persuasive word is able to project in the others a mask o f the being; this stays no able to be captured,since man, in this seek o f reality, takes with him the signs o f his senses and his own intelligibility. In this way, thatoriginal experience o f the intellibility ofthe founding word o f being is broken.